2014
DOI: 10.1017/s1473550413000268
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenetic characterization of the bacterial assemblage of Hot Lake, WA, an environment with high concentrations of magnesium sulphate, and its relevance to Mars

Abstract: Hot Lake (Oroville, WA) is an athalassohaline epsomite lake that can have precipitating concentrations of MgSO4 salts, mainly epsomite. Little biotic study has been done on epsomite lakes and it was unclear whether microbes isolated from epsomite lakes and their margins would fall within recognized halotolerant genera, common soil genera, or novel phyla. Our initial study cultivated and characterized epsotolerant bacteria from the lake and its margins. Approximately 100 aerobic heterotrophic microbial isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 65 publications
3
33
0
Order By: Relevance
“…The latter are aerobes that grow optimally at mesophilic temperatures, and likely their low abundance reflected the anoxic nature of our sediment samples and the temperate environment. The lack of Cyanobacteria, and indeed any phototroph, in our samples was surprising given that they thrive in the water of nearby Hot Lake (Lindemann et al, 2013 ; Kilmer et al, 2014 ), and have been observed within the salt crusts of Spotted Lake (Cannon, pers. comm .).…”
Section: Discussionmentioning
confidence: 77%
“…The latter are aerobes that grow optimally at mesophilic temperatures, and likely their low abundance reflected the anoxic nature of our sediment samples and the temperate environment. The lack of Cyanobacteria, and indeed any phototroph, in our samples was surprising given that they thrive in the water of nearby Hot Lake (Lindemann et al, 2013 ; Kilmer et al, 2014 ), and have been observed within the salt crusts of Spotted Lake (Cannon, pers. comm .).…”
Section: Discussionmentioning
confidence: 77%
“…The observed Ca-/Mg-sulfate and chloride assemblages are predicted to result from alteration of Martian basalts to produce sulfate-and chloride-rich but iron-poor brines 1 [37][38][39] and crystallization of sulfate salts may also aid preservation of biosignatures 40 .…”
Section: Climatic Variabilitymentioning
confidence: 99%
“…Table 1. Salinotolerant bacteria used for this study from Hot Lake (Kilmer et al 2014) and the Great Salt Plains (Caton et al 2004) Isolate Identification GenBank accession…”
Section: Media and Growth Measurementsmentioning
confidence: 99%